PREPARATION OF ALGINATE â PAPAYA SEED POWDER - FE3O4 COMPOSITE AS ADSORBENT FOR PB(II) ION - Pamanda Turnip, Berkat
Pb(II) metal ion is a heavy metal pollutant that contaminates waters. This metal is dangerous for aquatic ecosystems because it has the potential to cause poisoning and is mutagenic, triggering tumors, cancer and even death. According to WHO, the safe threshold for Pb(II) ion concentration is 0.1 ppm. The removal of Pb(II) ions from the waters can be carried out by various methods, one of which is adsorption. This method is used because it is easy, effective and cheap. In this research, a composite of alginate-papaya seed powder-magnetite has been prepared as an adsorbent for Pb(II) ions. The adsorbent were characterized using FTIR and XRD. Based on the wave number shift pattern in the FTIR spectrum, Pb(II) ions interact with the hydroxy and carbonyl groups on the adsorbent. XRD characterization results show that magnetite has an average particle size of 9,56 nm and a degree of crystallinity of 43,18%. The adsorption process of Pb(II) ions reached optimum conditions at pH 4, contact time of 4 hours and the mass ratio of alginate and papaya seed powder was 2:1. The adsorption process followed the pseudo-second-order reaction kinetics model and the Langmuir adsorption isotherm model with a qmax value of 11.93 mg/g. Adsorption thermodynamic studies show that the adsorption process occurs spontaneously and endothermic.